Neošamanistlikest vabavormidest Lõuna-Siberi põlisrahvaste näitel - Tenno, Indrek (Usuteaduslik Ajakiri, 2020)
On the Free Forms of Neoshamanism Based on the Indigenous Peoples of Southern Siberia Starting from the second half of the 1980s, the indigenous areas of Southern Siberia in the Soviet Union saw the beginning of the liberation movement know as perestroika, which brought on in the region an active, versatile and purposeful restoration of shamanism – the historic religion of the peoples of Southern Siberia. This article explores the new shamanistic forms and practices characteristic only to Southern Siberia formed during these processes, which have common features with similar trends that occurred in other parts of the world. The research methods used in this article include the synthesis and meta-analytic comparison of the data obtained from source materials, which has been the basis for drawing general conclusions giving an overview of the modern specificities and characteristics of neoshamanism in Southern Siberia.